Slavic and Eastern-European Visuality Modernity and Tradition - Ioffe, Dennis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Special Issue of Arts: "Slavic and Eastern-European Visuality: Modernity and Tradition" is focused on researching interactions of art and literature, of philosophy and visual poetry, and generally on theoretical aspects of cultural analysis.